Effect of sub lethal concentration of mercury and copper on oxygen consumption of fresh water crab, Barytelphusa guerini. - Mukke, V K; Chinte, D N (Recent Research in Science and Technology, 2012)
The seasonal effect of heavy metals mercury and copper on the oxygen consumption of fresh water crab, Barytelphusa guerini was studied for long term exposure (i.e. 10, 20 and 30 days). The effect of both the metals were observed after exposure to sub lethal concentration (1/10th of 96hrs LC50) of HgCl2 and CuSO4 was 0.275, 0.250, 0.225, 0.20 ppm and 1.4, 1.35, 1.30, 1.25 ppm for monsoon. The concentrations were 0.30, 0.275, 0.25, 0.225 ppm and 1.45, 1.4, 1.35, 1.30 ppm for winter and 0.175, 0.14, 0.125, 0.115 ppm and 0.9, 0.85, 0.80 and 0.75 ppm summer season. Present investigation reveals that the rate of oxygen consumption decreased with an increase in exposure period and depends upon time of exposure and concentration of toxicants. Mercury was found high toxic than that of copper in all the seasons. The order of decrease in rate of O2 consumption was summer > monsoon> winter season respectively.